Desarrollo e implementación de un diccionario-traductor del idioma kichwa a español para niños de educación básica de la escuela José Antonio Erique de la ciudad de Loja. - Tacuri Quezada, Alberto (2016)
The technological development demands the use of software applications to enhance the pedagogical support into the different knowledge areas since first years of elementary school. These media applications allow students to develop skills according to information and communication tecnologies and also, shortens the time that takes the teaching-learning process inside the class. The present graduation work, implements a pedagogical support system for Kichwa language teaching. The software development technology used is ICONIX, based on a set of sistematic activities during the development and user requirement programming until reaching complete satisfaction level. ICONIX uses UML, featured by interactive and incremental, and also sistematically develops process taking into account user requirements. For the development of this application, it was used Java, Java Media, Framework, MySql y Multimedia. Data collection was made through surveys which mainly were used to raise user requirements and the tests were made with real users teachers and children to check on how friendly the system was to them and also if it was according to all their requirements, this process was previous the final application implementation. After the test period, it was possible to make the corrections and optimize the tools available in the application so, it was perfect to users and creators. The goal was reached and it was possible to implement a translator dictionary Kichwa-Spanish, which will be able to give academic support and the teaching-learning process will be much easier and better for children of general elementary schools around the country where Kichwa language teaching takes place, because terms may chance according to a specific Kichwa dialect used in their region.